Pengaruh Pertumbuhan Ekonomi dan Pertumbuhan Penduduk Terhadap Tingkat Pengangguran di Kabupaten Mimika - Taime, Habel; Djaelani, Putri Nadya (STIE Jambatan Bulan, 2021)
This study aims to determine the significance of the influence of economic growth and population growth on the unemployment rate in Mimika Regency. The method in this study is an associative method using multiple linear regression analysis tools with the help of SPSS statistic. Based on the results obtained in this study, the value of regression coefficient in economic growth variable was 0.058. The coefficient of positive value means that there is a positive relationship between economic growth and the unemployment rate. Then the coefficient of regression in the population growth variable was 0.451. The coefficient of positive value means that there is a positive relationship between population growth and the unemployment rate.